Prevalence and risk factors of cosmetic-induced adverse events: A systematic review and meta-analysis - Sweta Kumari, Tambe Daniel Atem, Vaibhav Chaudhary, Sanjeev Kumar Sahu, Biplab Pal (Journal of Applied Pharmaceutical Science, 2024)
Cosmetic usage has seen a significant surge globally, driven by the desire for aesthetic enhancement. However, with this increased usage, there is a rising concern regarding adverse events associated with cosmetic products. The objective of this study was to evaluate the prevalence and risk factors of cosmetic-induced adverse events. The identification of primary studies was carried out using databases such as PubMed, Embase, Scopus, and Google Scholar. Included were studies published in English reporting the prevalence of adverse events due to various cosmetic products. Quality assessment was performed using the Joanna Briggs Institute checklist, and data extraction from primary studies utilized a standard template. Analysis was carried out using R software applying a random effects model with a 95% confidence interval. To assess determinants of cosmetic-induced adverse events, data were extracted from studies reporting adjusted odds ratios, with statistical significance observed. Out of the initially identified 1,306 unique citations, 23 articles met the inclusion criteria. The pooled prevalence of cosmetic-induced adverse events was found to be 41.1% (95% CI: 31.7; 51.1), with significant heterogeneity (I2 = 99%; p = 0). Subgroup analysis based on region revealed the highest prevalence in Africa (53.6%), followed by South America (38.0%), Asia (35.0%), and Europe (33.4%). Students exhibited a higher prevalence (51.1%) compared to the general population (36.8%). Sensitivity analysis confirmed the stability of the pooled prevalence. Egger’s test showed the presence of publication bias (p = 0.0414). The study highlighted a concerning prevalence of cosmetic-induced adverse events. The findings advocate for global cosmetovigilance, regulatory enhancements, and consumer awareness to ensure safer cosmetic usage.
Keywords: Cosmeceuticals, side effects, adverse effects, allergic reactions, cosmetovigilance, epidemiology